Fluorescent resin composition, fluorescent crack injection material, and crack injection repair method

By using a combination of fluorescent resin composition with free radical reactive resin and monomer, the bond strength and durability of existing repair materials are solved, and the repair process and historical records are visualized, which improves the repair effect.

JP2025016129APending Publication Date: 2025-01-31RESONAC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023119192
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

The existing repair materials do not have adhesive strength and durability after reacting with the resin, and cannot effectively monitor the repair process and history, resulting in poor repair results.

Method used

A fluorescent resin composition containing free radical reactive resin and free radical polymerized unsaturated monomer was used to emit light under ultraviolet light at 365 nm wavelength to reveal the repair process and record the repair history.

Benefits of technology

It provides fluorescent repair materials with high bond strength and durability, which can display repair processes and historical records under ultraviolet light, improving the visualization and management of repair effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016129000001
    Figure 2025016129000001
  • Figure 2025016129000002
    Figure 2025016129000002
  • Figure 2025016129000003
    Figure 2025016129000003
Patent Text Reader

Abstract

To provide a fluorescent radical composition using a fluorescent radical polymerizable compound (B1) having reactivity with a resin, a fluorescent crack injection material which is excellent in strength development property by using a fluorescent radical polymerizable compound, and a crack injection repair method which visualizes progress of injection work using a fluorescent crack injection material, and a crack repair management method which visualizes a repair history of a repair place.SOLUTION: A fluorescent radical resin composition contains a radical reactive resin (A) and a radical polymerizable unsaturated monomer (B). The radical polymerizable unsaturated monomer (B) contains a fluorescent radical polymerizable compound (B1).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fluorescent resin composition, a fluorescent crack injection material, and a crack injection repair method. [Background technology]

[0002] In recent years, the number of concrete structures requiring repair has been increasing. Concrete structures deteriorate due to neutralization, salt damage, and other factors. Concrete structures in cold regions in particular deteriorate rapidly due to the effects of chlorides such as calcium chloride and sodium chloride, which are used as snow-melting agents, as well as the freezing and thawing of water contained in the concrete. For this reason, there is a demand for repairs to be made as soon as possible for concrete structures.

[0003] There are cases where photosensitivity is given to injection materials for the purpose of advance detection and confirmation of repair history after construction, but in all cases, this is achieved by adding substances such as fluorescent dyes (for example, Patent Documents 1 to 4). These additives are components that do not react with resins and do not contribute to the physical properties of the crack injection material after hardening. Therefore, there is a concern that the hardening properties, adhesive strength, and durability of the crack injection material will decrease. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-235778 A [Patent Document 2] WO 16 / 006049 [Patent Document 3] JP 2013-079505 A [Patent Document 4] JP 2011-185629 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a resin composition that does not reduce adhesive strength and durability and can be visualized. Another aim is to provide a fluorescent crack injection material that is excellent in strength expression. Another aim is to provide a crack injection repair method that visualizes the progress of the injection work, and a crack repair management method that visualizes the repair history of the repair area. [Means for solving the problem]

[0006] That is, the present invention employs the following configuration. [1] A fluorescent resin composition comprising a radical-reactive resin (A) and a radical-polymerizable unsaturated monomer (B), wherein the radical-polymerizable unsaturated monomer comprises a fluorescent radical-polymerizable compound (B1). [2] The fluorescent resin composition according to [1], wherein the fluorescent radical polymerizable compound (B1) is a compound that emits fluorescence when irradiated with light having a wavelength of 365 nm. [3] The fluorescent resin composition according to [1] or [2], wherein the fluorescent radically polymerizable compound (B1) contained in the radically polymerizable unsaturated monomer (B) is 10 to 95 mass % relative to 100 mass % in total of the radically reactive resin (A) and the radically polymerizable unsaturated monomer (B). [4] The fluorescent resin composition according to any one of [1] to [3], wherein the fluorescent radical polymerizable compound (B1) is at least one selected from the group consisting of dicyclopentenyloxy methacrylate, acryloylmorpholine, phenoxyethyl methacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, 2-ethylhexyl methacrylate, and PEG#200 dimethacrylate. [5] The fluorescent resin composition according to any one of [1] to [4], further comprising a fluorescent surfactant. [6] A fluorescent crack injection material comprising the fluorescent resin composition according to any one of [1] to [5]. [7] A crack injection method comprising the steps of injecting the fluorescent crack injection material described in [6] into a crack in at least one structure selected from the group consisting of concrete, asphalt concrete, mortar, wood, and metal, and allowing it to harden. [8] A crack injection repair method, comprising injecting the fluorescent crack injection material described in [6] into cracks in at least one structure selected from the group consisting of concrete, asphalt concrete, mortar, wood, and metal, and irradiating the cracks with ultraviolet light to visualize the progress of the injection work. [9] A method for managing crack repair, comprising injecting the fluorescent crack injection material described in [6] into cracks in at least one structure selected from the group consisting of concrete, asphalt concrete, mortar, wood, and metal, allowing it to harden, and then irradiating the repair area with ultraviolet light to visualize the repair history. Effect of the Invention

[0007] According to the present invention, it is possible to provide a fluorescent resin composition using a fluorescent radical polymerizable compound. In addition, by using a fluorescent radical polymerizable compound, it is possible to provide a fluorescent crack injection material with excellent strength expression. Furthermore, it is possible to provide a crack injection repair method that visualizes the progress of the injection work using the fluorescent crack injection material, and a crack repair management method that visualizes the repair history of the repaired area. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The fluorescent resin composition, the fluorescent crack injection material, the crack injection repair method, and the crack repair management method of the present invention will be described in detail below.

[0009] [Fluorescent resin composition] A fluorescent resin composition according to one embodiment of the present invention (sometimes referred to as the fluorescent resin composition of the present embodiment) contains a radically reactive resin (A) and a radically polymerizable unsaturated monomer (B). The radically polymerizable unsaturated monomer (B) contains a fluorescent radically polymerizable compound (B1). The radically polymerizable unsaturated monomer (B) may contain a non-fluorescent radically polymerizable unsaturated monomer (B2) in addition to the fluorescent radically polymerizable compound (B1). The fluorescent resin composition of this embodiment may also contain an aromatic tertiary amine (C) and an organic peroxide (D). Furthermore, the fluorescent resin composition of this embodiment may contain a fluorescent surfactant (E).

[0010] "Radical reactive resin (A)" The radical reactive resin (A) has an ethylenic carbon-carbon double bond in a side chain and / or a main chain. The radical reactive resin (A) is preferably at least one selected from the group consisting of vinyl ester resins, urethane (meth)acrylate resins, and polyester (meth)acrylate resins.

[0011] (Vinyl ester resin) Vinyl ester resins are sometimes called epoxy (meth)acrylate resins. As vinyl ester resins, conventionally known ones obtained by esterification reaction of epoxy compounds with unsaturated monobasic acids (and saturated dibasic acids as necessary) can be used without any restrictions. Such known vinyl ester resins are described, for example, in "Polyester Resin Handbook," published by Nikkan Kogyo Shimbun, 1988, and "Paint Terminology Dictionary," edited by the Color Materials Association, 1993, and the like.

[0012] Examples of epoxy compounds used as a raw material for vinyl ester resins include a reaction product of bisphenol A and epichlorohydrin, a reaction product of hydrogenated bisphenol A and epichlorohydrin, a reaction product of cyclohexanedimethanol and epichlorohydrin, a reaction product of norbornane dialcohol and epichlorohydrin, a reaction product of tetrabromobisphenol A and epichlorohydrin, a reaction product of tricyclodecane dimethanol and epichlorohydrin, an alicyclic diepoxy carbonate, an alicyclic diepoxy acetal, an alicyclic diepoxy carboxylate, a novolac glycidyl ether, and a cresol novolac glycidyl ether.

[0013] Examples of unsaturated monobasic acids used as raw materials for vinyl ester resins include acrylic acid and methacrylic acid. Examples of the saturated dibasic acid used as a raw material for the vinyl ester resin include adipic acid, sebacic acid, and dimer acid.

[0014] In the present embodiment, the vinyl ester resin is preferably a bisphenol A vinyl ester resin from the viewpoint of flexibility and toughness of the cured product.

[0015] (Urethane (meth)acrylate resin) The urethane (meth)acrylate resin in this embodiment is a polyurethane having a radically reactive unsaturated group. Specifically, it is a radically reactive unsaturated group-containing oligomer obtained by reacting a polyisocyanate with a polyhydroxy compound or polyhydric alcohols, and then reacting the excess isocyanato group with a hydroxyl group-containing (meth)acrylic compound. In the above reaction, a hydroxyl group-containing allyl ether compound may be reacted together with the hydroxyl group-containing (meth)acrylic compound as necessary. In addition, the urethane (meth)acrylate resin may be produced by reacting a polyisocyanate with a polyhydroxy compound or polyhydric alcohols, and a hydroxyl group-containing (meth)acrylic compound, and then reacting the polyisocyanate with the unreacted hydroxyl group derived from the polyhydroxy compound or polyhydric alcohols. In this reaction, a hydroxyl group-containing allyl ether compound may be reacted together with the hydroxyl group-containing (meth)acrylic compound as necessary.

[0016] Examples of polyisocyanates used as raw materials for the urethane (meth)acrylate resin include 2,4-tolylene diisocyanate and its isomers, diphenylmethane diisocyanate, hexamethylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, dicyclohexylmethane diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, Burnock (registered trademark) D-750, CRISBON (registered trademark) NK (trade name; manufactured by Dainippon Ink and Chemicals, Inc.), Desmodur (registered trademark) L (trade name; manufactured by Sumitomo Bayer), Coronate L (trade name; manufactured by Nippon Polyurethane Co., Ltd.), Takenate D102 (trade name; manufactured by Takeda Pharmaceutical Co., Ltd.), Isonate 143L (trade name; manufactured by Mitsubishi Chemical Corporation), and Duranate (registered trademark) series (trade name; manufactured by Asahi Kasei Chemical Co., Ltd.). These polyisocyanates may be used alone or in combination of two or more. Among these, diphenylmethane diisocyanate is preferred from the viewpoint of cost.

[0017] Examples of polyhydroxy compounds used as raw materials for the urethane (meth)acrylate resin include polyester polyols and polyether polyols. More specifically, examples include glycerin-ethylene oxide adducts, glycerin-propylene oxide adducts, glycerin-tetrahydrofuran adducts, glycerin-ethylene oxide-propylene oxide adducts, trimethylolpropane-ethylene oxide adducts, trimethylolpropane-propylene oxide adducts, trimethylolpropane-tetrahydrofuran adducts, trimethylolpropane-ethylene oxide-propylene oxide adducts, dipentaerythritol ethylene oxide adducts, dipentaerythritol propylene oxide adducts, dipentaerythritol tetrahydrofuran adducts, and dipentaerythritol ethylene oxide-propylene oxide adducts. These polyhydroxy compounds may be used alone or in combination of two or more.

[0018] Examples of polyhydric alcohols used as raw materials for the urethane (meth)acrylate resin include ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, 1,3-butanediol, an adduct of bisphenol A with propylene oxide or ethylene oxide, 1,2,3,4-tetrahydroxybutane, glycerin, trimethylolpropane, 1,3-butanediol, 1,2-cyclohexane glycol, 1,3-cyclohexane glycol, 1,4-cyclohexane glycol, paraxylene glycol, bicyclohexyl-4,4-diol, 2,6-decalin glycol, 2,7-decalin glycol, etc. These polyhydric alcohols may be used alone or in combination of two or more.

[0019] The hydroxyl group-containing (meth)acrylic compound used as the raw material of the urethane (meth)acrylate resin is preferably a hydroxyl group-containing (meth)acrylic acid ester.Specific examples include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, di(meth)acrylate of tris(hydroxyethyl)isocyanuric acid, pentaerythritol tri(meth)acrylate, glycerin (mono)(meth)acrylate, and Blemmer (registered trademark) series (trade name; manufactured by NOF Corp.).These hydroxyl group-containing (meth)acrylic compounds may be used alone or in combination of two or more.

[0020] Specific examples of the hydroxyl group-containing allyl ether compound used as necessary as a raw material for the urethane (meth)acrylate resin include ethylene glycol monoallyl ether, diethylene glycol monoallyl ether, triethylene glycol monoallyl ether, polyethylene glycol monoallyl ether, propylene glycol monoallyl ether, dipropylene glycol monoallyl ether, tripropylene glycol monoallyl ether, polypropylene glycol monoallyl ether, 1,2-butylene glycol monoallyl ether, 1,3-butylene glycol monoallyl ether, hexylene glycol monoallyl ether, octylene glycol monoallyl ether, trimethylolpropane diallyl ether, glycerin diallyl ether, pentaerythritol triallyl ether, etc. These hydroxyl group-containing allyl ether compounds may be used alone or in combination of two or more.

[0021] (Polyester (meth)acrylate resin) The polyester (meth)acrylate resin in this embodiment is a polyester having a (meth)acryloyloxy group. The polyester (meth)acrylate resin can be produced, for example, by any one of the production methods (1) to (3) shown below.

[0022] (1) A polyester having a carboxyl group at the end, which is obtained from at least one of a saturated polybasic acid and an unsaturated polybasic acid and a polyhydric alcohol, is reacted with an epoxy compound containing an α,β-unsaturated carboxylate group. (2) A hydroxyl group-containing (meth)acrylate is reacted with a polyester having a carboxyl group at the end, which is obtained from at least one of a saturated polybasic acid and an unsaturated polybasic acid and a polyhydric alcohol. (3) A polyester having a hydroxyl group at the end, which is obtained from at least one of a saturated polybasic acid and an unsaturated polybasic acid and a polyhydric alcohol, is reacted with (meth)acrylic acid.

[0023] Examples of saturated polybasic acids used as raw materials for polyester (meth)acrylate resins include polybasic acids that do not have a polymerizable unsaturated bond, such as phthalic acid, isophthalic acid, terephthalic acid, tetrahydrophthalic acid, adipic acid, and sebacic acid, or anhydrides thereof. Examples of unsaturated polybasic acids used as raw materials for polyester (meth)acrylate resins include fumaric acid, maleic acid, itaconic acid, and anhydrides thereof.

[0024] Examples of polyhydric alcohol components used as raw materials for polyester (meth)acrylate resins include ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, 1,2-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, cyclohexane-1,4-dimethanol, an ethylene oxide adduct of bisphenol A, and a propylene oxide adduct of bisphenol A.

[0025] A representative example of an epoxy compound containing an α,β-unsaturated carboxylic acid ester group that is used as a raw material for polyester (meth)acrylate resins is glycidyl methacrylate. In the present embodiment, the polyester (meth)acrylate resin is preferably a bisphenol A type polyester (meth)acrylate resin from the viewpoint of mechanical strength.

[0026] <Radical polymerizable unsaturated monomer (B)> The radical polymerizable unsaturated monomer (B) according to the present embodiment includes a fluorescent radical polymerizable compound (B1). The radical polymerizable unsaturated monomer (B) may include a non-fluorescent radical polymerizable unsaturated monomer (B2) in addition to the fluorescent radical polymerizable compound (B1). The radically polymerizable unsaturated monomer (B) is preferably a radically polymerizable unsaturated compound having a (meth)acryloyloxy group in the molecule. In this embodiment, the term "(meth)acryloyloxy group" means "one or both of an acryloyloxy group and a methacryloyloxy group." In this embodiment, the term "(meth)acrylate" means "one or both of an acrylate and a methacrylate."

[0027] <Fluorescent radically polymerizable compound (B1)> The fluorescent radical polymerizable compound (B1) according to the present embodiment is not particularly limited as long as it is a radical polymerizable compound having fluorescence that emits fluorescence when irradiated with ultraviolet light (hereinafter also referred to as "UV"). The fluorescent radical polymerizable compound (B1) is preferably a radical polymerizable compound that emits fluorescence when irradiated with light having a wavelength of 365 nm. In addition, the fluorescent radical polymerizable compound (B1) is preferably a radical polymerizable unsaturated compound having a (meth)acryloyloxy group in the molecule.

[0028] Examples of the fluorescent radically polymerizable compound (B1) include dicyclopentenyloxy methacrylate, acryloylmorpholine, phenoxyethyl methacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, 2-ethylhexyl methacrylate, and PEG#200 dimethacrylate. Among these, dicyclopentenyloxy methacrylate and diethylene glycol dimethacrylate have strong fluorescence and are therefore preferred in terms of evaluating the repair history. In addition, from the viewpoint of exerting toughness on the cured product of the resin component, acryloylmorpholine and 2-ethylhexyl methacrylate are preferred, and acryloylmorpholine is particularly preferred.

[0029] <Non-fluorescent radically polymerizable unsaturated monomer (B2)> The radical polymerizable unsaturated monomer (B) has a lower viscosity than the radical reactive resin (A). Therefore, the radical polymerizable unsaturated monomer (B) lowers the viscosity of the resin component, making the viscosity of the resin composition a preferable viscosity that makes it easy to inject into cracks in structures when used as a crack injection material. In addition, the radical polymerizable unsaturated monomer (B) is important for ensuring the hardness, strength, chemical resistance, and water resistance of the cured product of the resin composition containing it.

[0030] The non-fluorescent radically polymerizable unsaturated monomer (B2) in this embodiment is a radically polymerizable unsaturated monomer other than the fluorescent radically polymerizable compound (B1), and is not particularly limited, but is preferably a radically polymerizable unsaturated compound having a (meth)acryloyloxy group in the molecule. Examples of non-fluorescent radically polymerizable unsaturated monomers include (meth)acrylic acid monoalkyl esters, (meth)acrylic acid dialkyl esters, (meth)acrylic acid trialkyl esters, etc. Specific examples include methoxyethyl (meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, tricyclodecane di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and 1,4-butanediol di(meth)acrylate. , 1,6-Hexanediol di(meth)acrylate, 1,9-Nonanediol di(meth)acrylate, Neopentyl glycol di(meth)acrylate, Glycerin di(meth)acrylate, Ethoxylated polypropylene glycol di(meth)acrylate, Trimethylolpropane tri(meth)acrylate, Ethoxylated isocyanuric acid tri(meth)acrylate, ε-Caprolactone modified tris-(2-acryloxyethyl)isocyanurate, Pentaerythritol dimethacrylate, Lithritol tri(meth)acrylate, dimethylolpropane tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, dipentaerythritol poly(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 2,2-bis[4-(methacryloxyethoxy)phenyl]propane, 2,2-bis[4-(methacryloxy-diethoxy)phenyl]propane, 2,2-bis[4-(methacryloxy-poly(meth)acrylate)] 2,2-bis[4-(acryloxy-diethoxy)phenyl]propane, 2,2-bis[4-(acryloxy-polyethoxy)phenyl]propane, styrene monomer, α-, o-, m-, p-alkyl, nitro, cyano, amide, ester derivatives of styrene, chlorostyrene, vinyltoluene, divinylbenzene and other styrene-based monomers; butadiene, 2,3-dimethylbutadiene, isoprene, chloroprene and other dienes;Examples of the (meth)acrylic acid esters include ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, dodecyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, tetrahydrofuryl (meth)acrylate, acetoacetoxyethyl (meth)acrylate, and dicyclopentenyl (meth)acrylate; and acrylic acids having heterocyclic amines such as (meth)acryloylmorpholine. Condensates of unsaturated acids such as maleic acid, fumaric acid, and itaconic acid with alcohols can also be used.

[0031] Among these, trimethylolpropane tri(meth)acrylate, lauryl (meth)acrylate, methyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and methoxyethyl (meth)acrylate are particularly preferred from the viewpoints of workability and compressive strength.

[0032] The radical reactive resin (A) component and the radical polymerizable unsaturated monomer (B) component constituting the fluorescent resin composition of this embodiment are collectively referred to as the resin component (hereinafter, may be simply referred to as the resin component). In the resin component, it is preferable that the radical reactive resin (A) is 5 to 65 mass % and the radical polymerizable unsaturated monomer (B) is 35 to 95 mass %. More preferably, the radical reactive resin (A) is 5 to 50 mass % and the radical polymerizable unsaturated monomer (B) is 50 to 95 mass %, and even more preferably, the radical reactive resin (A) is 5 to 40 mass % and the radical polymerizable unsaturated monomer (B) is 60 to 95 mass %.

[0033] When the radical polymerizable unsaturated monomer (B) contained in the resin component is 35% by mass or more (radical reactive resin (A) is 65% by mass or less), the viscosity of the resin component becomes lower. As a result, when the resin composition is used as a crack injection material, the viscosity becomes a viscosity that is easier to inject into cracks in structures. On the other hand, when the radical polymerizable unsaturated monomer (B) is 95% by mass or less (radical reactive resin (A) is 5% by mass or more), the cured product of the resin composition has high strength. As a result, when the resin composition is used as a crack injection material, the structure in which the cracks are repaired by injection exhibits good strength, which is preferable.

[0034] The viscosity of the resin component at 25° C. is preferably 150 mPa·s or less, and more preferably 100 mPa·s or less. If the viscosity of the resin component at 25° C. is 150 mPa·s or less, the viscosity of the resin component at -10° C. will be 2000 mPa·s or less. Therefore, when the resin composition is used as a crack injection material, the crack injection material has excellent workability during injection even in a low-temperature environment of -10° C. or less. The lower limit of the viscosity of the resin component at 25° C. is preferably 0.5 mPa·s or more, and more preferably 10 mPa·s or more. When the resin composition has a viscosity of 0.5 mPa·s or more at 25° C., when the resin composition is used as a crack injection material, the amount of the crack injection material injected into the crack that leaks from the watertight portion applied to the crack other than the injection hole is small, which is preferable.

[0035] In this embodiment, "workability during injection" refers to the ease of injecting a crack injection material containing a resin composition into cracks in a concrete structure or the like.

[0036] In this embodiment, the fluorescent radical polymerizable compound (B1) is preferably 10% by mass or more relative to the total amount of the radical reactive resin (A) and the radical polymerizable unsaturated monomer (B) (100% by mass) in order to exhibit fluorescence and evaluate the repair history, more preferably 20% by mass or more, even more preferably 30% by mass or more, and even more preferably 50% by mass or more. In addition, in order to ensure the development of strength as a crack injection material, it is preferably 95% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less. The range of the content of the fluorescent radical polymerizable compound (B1) in the resin component can be a combination of any of the above lower limit value and the above upper limit value, but is preferably 10 to 95% by mass, preferably 20 to 80% by mass, more preferably 30 to 70% by mass, and even more preferably 50 to 70% by mass. When it is in the above range, when injection work is performed using the fluorescent crack injection material, the development of strength is ensured and the progress of the work is easily visualized. In addition, when a fluorescent radical polymerizable compound is contained in the radical polymerizable unsaturated monomer that is the raw material of the radical reactive resin (A), it is counted as the fluorescent radical polymerizable compound (B1) as the radical polymerizable unsaturated monomer.

[0037] <Aromatic tertiary amine (C)> In this embodiment, the aromatic tertiary amine (C) functions as a curing accelerator for the resin composition.

[0038] Examples of the aromatic tertiary amine (C) in this embodiment include N-methyl-N-β-hydroxyethyl aniline, N-butyl-N-β-hydroxyethyl aniline, N-methyl-N-β-hydroxyethyl-p-toluidine, N-butyl-N-β-hydroxyethyl-p-toluidine, N-methyl-N-β-hydroxypropyl aniline, N-methyl-N-β-hydroxypropyl-p-toluidine, N,N-di(β-hydroxyethyl)aniline, N,N-di(β-hydroxypropyl)aniline, N,N-di(β-hydroxyethyl)-p-toluidine, N,N-di(β-hydroxypropyl)-p-toluidine, N,N-diisopropylol-p-toluidine, N,N-di(β-hydroxyethyl)-p-anisidine, N,N-dimethylaniline, and N,N-dimethyl-p-toluidine.

[0039] Among the above aromatic tertiary amines (C), N,N-di(β-hydroxyethyl)-p-toluidine and N,N-di(β-hydroxypropyl)-p-toluidine are particularly preferred from the viewpoint of low-temperature curing properties. The aromatic tertiary amine (C) may be used alone or in combination of two or more kinds.

[0040] In the resin composition of the present embodiment, the aromatic tertiary amine (C) is preferably contained in an amount of 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, per 100 parts by mass of the resin component. When the content of the aromatic tertiary amine (C) per 100 parts by mass of the resin component is 0.1 parts by mass or more, the curability of the resin composition in a low-temperature environment becomes even better. In addition, when the content of the aromatic tertiary amine (C) per 100 parts by mass of the resin component is 10 parts by mass or less, the aromatic tertiary amine (C) does not affect the workability during injection when the resin composition is used as a crack injection material, which is preferable.

[0041] <Organic peroxide (D)> The organic peroxide (D) acts as a radical polymerization initiator. As the organic peroxide (D), a known organic peroxide is used.

[0042] Specific examples of organic peroxides (D) include benzoyl peroxide, dicumyl peroxide, diisopropyl peroxide, di-t-butyl peroxide, t-butyl peroxybenzoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3, 3-isopropyl hydroperoxide, t-butyl hydroperoxide, dicumyl peroxide, dicumyl hydroperoxide, and acetyl peroxide. peroxide, bis(4-t-butylcyclohexyl) peroxydicarbonate, diisopropyl peroxydicarbonate, isobutyl peroxide, 3,3,5-trimethylhexanoyl peroxide, lauryl peroxide, azobisisobutyronitrile, azobiscarbonamide, benzoyl m-methylbenzoyl peroxide, m-toluoyl peroxide, methyl ethyl ketone peroxide, cumene hydroperoxide, and t-butyl peroxybenzoate.

[0043] Among these organic peroxides (D), at least one selected from the group consisting of dibenzoyl peroxide, benzoyl m-methylbenzoyl peroxide, m-toluoyl peroxide, methyl ethyl ketone peroxide, cumene hydroperoxide and t-butyl peroxybenzoate is particularly preferred.

[0044] In the resin composition of the present embodiment, the organic peroxide (D) is preferably contained in an amount of 0.1 to 10 parts by mass, more preferably 2 to 8 parts by mass, relative to 100 parts by mass of the resin component. When the content of the organic peroxide (D) relative to 100 parts by mass of the resin component is 0.1 parts by mass or more, the curing of the resin composition proceeds sufficiently, which is preferable. In addition, when the content of the organic peroxide (D) relative to 100 parts by mass of the resin component is 10 parts by mass or less, it is economical. In addition, when the content of the organic peroxide (D) is 10 parts by mass or less, poor curing due to the influence of the plasticizer contained in the organic peroxide (D) can be avoided. As a result, the physical properties such as strength and toughness of the cured product of the resin composition are further improved, which is preferable.

[0045] <Fluorescent Surfactant (E)> Examples of fluorescent surfactants include ammonium polyoxyethylene styrenated phenyl ether sulfate such as Hitenol NF-08, Hitenol NF-13, and Hitenol NF-17, all of which are manufactured by Daiichi Kogyo Seiyaku Co., Ltd.; ammonium polyoxyethylene oleyl cetyl ether sulfate such as Hitenol NF-08E; ammonium polyoxyethylene lauryl ether sulfate such as Hitenol LA-10 and Hitenol LA-12; ammonium polyoxyethylene styrenated propenyl phenyl ether sulfate such as Aqualon AR-10; polyoxyethylene styrenated propenyl phenyl ether such as Aqualon AN-10; ammonium polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate such as Aqualon KH-05 and Aqualon KH-10; and polyoxyethylene-1-(allyloxymethyl) alkyl ether such as Aqualon KN-10. Among these, Hitenol NF-08 and Aqualon AR-10 are preferable in terms of improving adhesion to wet surfaces. For the purpose of improving the adhesion of the surfactant to a wet surface, the amount of the surfactant is preferably 1 part by mass or more, and more preferably 3 parts by mass or more, per 100 parts by mass of the resin component. From the viewpoint of suppressing a decrease in strength and toughness in a cured product of the resin component, the amount of the surfactant is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less.

[0046] <Optional ingredients> The resin composition of this embodiment may contain polymerization inhibitors, waxes, thixotropic agents, reinforcing materials, coupling agents, curing accelerators, non-fluorescent surfactants, and the like, as long as the effects of the present invention are not impaired.

[0047] Examples of the polymerization inhibitor include hydroquinone, methylhydroquinone, trimethylhydroquinone, tertiary butyl catechol, and 2,6-di-tertiary butyl 4-methylphenol. Among them, 2,6-di-tertiary butyl 4-methylphenol is preferred because it is easily mixed with the resin. The polymerization inhibitor is preferably blended in an amount of 0.0001 to 10 parts by mass per 100 parts by mass of the resin component.

[0048] Waxes are blended for the purpose of improving the drying property of the resin composition. Any known waxes can be used without limitation. For example, petroleum wax (paraffin wax, microcrystalline wax, etc.), vegetable wax (candelilla wax, rice wax, wood wax, etc.), animal wax (beeswax, spermaceti, etc.), mineral wax (montan wax, etc.), synthetic wax (polyethylene wax, amide wax, etc.) can be used.

[0049] Specific examples of waxes include paraffin wax having a melting point of about 20°C to 80°C, BYK-S-750 (product name, manufactured by BYK-Chemie), BYK-S-740 (product name, manufactured by BYK-Chemie), and BYK-LP-S6665 (product name, manufactured by BYK-Chemie). Waxes may be used in combination of two or more waxes having different melting points. Paraffin wax may also be used in combination with a drying agent as described in JP-A-2002-97233. In this case, the effect of including paraffin wax can be more effectively brought out.

[0050] The wax is preferably contained in an amount of 0.1 to 5.0 parts by mass per 100 parts by mass of the resin component. By setting the wax content within the above range, the resin composition has good drying properties, and the deterioration of the physical properties of the cured product of the resin composition due to the inclusion of the wax can be prevented.

[0051] In addition, a solvent can be used to improve the solubility and dispersibility of the paraffin wax. Known solvents can be used. Examples of the solvent include alkyl ether acetates such as ethyl acetate, ethers such as tetrahydrofuran, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, hydrocarbons such as benzene, toluene, xylene, octane, decane, and dodecane, petroleum solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha, lactate esters such as methyl lactate, ethyl lactate, and butyl lactate, dimethylformamide, and N-methylpyrrolidone.

[0052] The thixotropic agent is blended for the purpose of imparting thixotropy. As the thixotropic agent, inorganic or organic agents may be used. For example, inorganic thixotropic agents include silica powder (Aerosil type), mica powder, calcium carbonate powder, and short fiber asbestos. As organic thixotropic agents, known agents such as hydrogenated castor oil are used. As the thixotropic agent, silica-based thixotropic agents are preferred. Silica powder (Aerosil type) may be used in combination with a thixotropic assistant such as BYK R605 (trade name, manufactured by BYK-Chemie).

[0053] Examples of reinforcing materials include fine powders of carbon, glass, ceramics, stainless steel, and the like.

[0054] As the coupling agent, a known one can be used, and as the coupling agent, a silane coupling agent such as aminosilane, vinylsilane, epoxysilane, or acrylsilane is preferable.

[0055] The curing accelerator is not particularly limited, but may be β-diketones such as acetylacetone, ethyl acetoacetate, α-acetyl-γ-butyrolactone, N-pyridininoacetoacetamide, and N,N-dimethylacetoacetamide. In the resin composition of the present embodiment, it is preferable not to use a metal salt as a curing accelerator from the viewpoint of storage stability. When the resin composition contains a metal salt, it is preferable to make it 1000 ppm or less in order to ensure storage stability.

[0056] Examples of non-fluorescent surfactants include anionic surfactants made of polyoxyethylene oleyl cetyl ether sulfate ester ammonium, such as Hitenol 08E manufactured by Daiichi Kogyo Seiyaku Co., Ltd., nonionic surfactants made of polyoxyethylene styrenated phenyl ether, such as Noigen EA-017 and EA-87, and cationic surfactants, such as Nissan Cation manufactured by NOF Corporation. In order for the surfactant to exhibit improved adhesion to wet surfaces, it is preferable that the amount of the surfactant is 1 part by mass or more, and more preferably 3 parts by mass or more, per 100 parts by mass of the resin component. In order to suppress the decrease in strength and toughness in the cured product of the resin component, it is preferable that the amount of the surfactant is 10 parts by mass or less, and more preferably 5 parts by mass or less.

[0057] The viscosity of the resin composition of this embodiment at 25°C is preferably 150 mPa·s or less, more preferably 100 mPa·s or less. When the viscosity of the resin composition at 25°C is 150 mPa·s or less, the viscosity of the resin composition at -10°C is 2000 mPa·s or less. Therefore, when the resin composition is used as a crack injection material, it becomes a crack injection material that has excellent workability during injection even in a low-temperature environment of -10°C or less. In addition, when the viscosity of the resin composition at 25°C is 150 mPa·s or less, when the resin composition is used as a crack injection material, it is easy to penetrate into fine gaps in cracks. Therefore, the hardened product obtained by hardening the crack injection material is also formed in the fine gaps in the cracks. As a result, a structure in which cracks are injected and repaired with the crack injection material exhibits better strength.

[0058] The lower limit of the viscosity of the resin composition at 25° C. is preferably 1.0 mPa·s or more, and more preferably 10 mPa·s or more. When the resin composition has a viscosity of 1.0 mPa·s or more at 25° C., when the resin composition is used as a crack injection material, the amount of the crack injection material injected into the crack that leaks out from the watertight portion applied to the crack other than the injection hole is small, which is preferable.

[0059] The resin composition of this embodiment contains the resin components described above. The resin composition of this embodiment has a viscosity that allows it to be easily injected into cracks in structures even in a low-temperature environment of -10°C or less, and can be cured in a short time. Furthermore, the cured product of the resin composition of this embodiment has good adhesive strength, making it suitable as a material for crack injection into structures. In particular, the cured product of the resin composition of this embodiment has good adhesive strength to materials containing mortar, such as concrete, asphalt concrete, and mortar. Therefore, the resin composition of this embodiment is suitable as a material for crack injection into concrete structures. In addition, since the resin composition of the present embodiment does not require the use of a metal salt as a curing accelerator, it has superior storage stability compared to a resin composition that contains a metal salt as a curing accelerator.

[0060] [Fluorescent crack injection material] The fluorescent crack injection material of one embodiment of the present invention (sometimes referred to as the fluorescent crack injection material of this embodiment) contains the fluorescent resin composition of this embodiment described above. The fluorescent crack injection material of this embodiment is preferably a two-component type which is stored separately as a first liquid containing a radical-reactive resin, a fluorescent radical-polymerizable compound (B1) as a radical-polymerizable unsaturated monomer, and, if necessary, an aromatic tertiary amine (C) represented by the above general formula (I), and a second liquid containing an organic peroxide (D), and which is mixed with the first liquid and second liquid when used.

[0061] The fluorescent crack injection material of this embodiment can be used to inject and repair cracks that have occurred in structures made of at least one material selected from the group consisting of concrete, asphalt concrete, mortar, wood, and metal. The crack injection material of this embodiment contains the above-mentioned resin composition that has good adhesive strength to materials containing cement. For this reason, it is particularly suitable for injecting and repairing cracks in structures made of materials containing cement such as concrete, asphalt concrete, and mortar, and structures made of materials containing cement and wood and / or metal.

[0062] When the fluorescent crack injection material of this embodiment is a two-component type, a cured product with excellent strength expression can be formed within 24 hours by mixing the first and second liquids and then leaving them in an environment at -10° C. When the crack injection material of this embodiment is a two-component type, a cured product with excellent strength expression can be formed within 48 hours by mixing the first and second liquids and then leaving them in an extremely low-temperature environment at -20° C.

[0063] The fluorescent crack injection material of this embodiment may contain the fluorescent radical resin composition of this embodiment. Therefore, the fluorescent crack injection material of this embodiment may be composed of only the fluorescent resin composition of this embodiment, or may contain other components in addition to the fluorescent radical resin composition of this embodiment. Examples of other components include components contained in known crack injection materials.

[0064] [Crack injection method] A crack injection method of one embodiment of the present invention (sometimes referred to as the crack injection method of the present embodiment) comprises the steps of injecting and hardening the fluorescent crack injection material of the present embodiment into a crack that has occurred in at least one structure selected from the group consisting of concrete, asphalt concrete, mortar, wood, and metal.

[0065] [Crack injection repair method] In the crack injection repair method of this embodiment, when a two-component fluorescent crack injection material is used, first, a first liquid containing a resin component and the aromatic tertiary amine (C) represented by the above general formula (I) is mixed with a second liquid containing an organic peroxide (D) to prepare the crack injection material.

[0066] Next, the above-mentioned crack injection material is injected into cracks in at least one structure selected from the group consisting of concrete, asphalt concrete, mortar, wood, and metal, and the progress of the injection work is visualized by irradiating it with UV light.

[0067] A known method can be used for UV irradiation, for example, a method of irradiating a structure with a lamp having a light source in the range of 300 nm to 400 nm. A specific example of the light source is UVGL-58 manufactured by Funakoshi, which is a UV lamp having a wavelength of 365 nm. However, the UV lamp may contain a wavelength other than 365 nm.

[0068] The method of injecting the crack grout into cracks in a structure is not particularly limited, but may be, for example, a method of directly injecting the crack into the cracks in the structure using a cylinder, etc. Alternatively, a method of injecting the crack grout may be used in which a crack inflow agent is applied to the surface of a structure having cracks using a tool such as a spray, roller, brush, paint brush, or spatula, and the crack grout is allowed to penetrate and be injected into the cracks. The crack grout material thus injected into the cracks of the structure is left in the cracks and hardens into a hardened material.

[0069] In the crack injection repair method of this embodiment, the above-mentioned crack injection material is used, so it can harden in a short time even in a low-temperature environment of -10° C. or less. Therefore, crack injection repair work for structures can be efficiently performed even in a low-temperature environment of -10° C. or less. In addition, in the crack injection repair method of this embodiment, the above-mentioned crack injection material having good adhesive strength is used, so that the structure in which the cracks have been injected and repaired exhibits good strength.

[0070] [How to manage crack repairs] The crack repair management method of this embodiment is characterized in that the UV-sensitive crack injection material described in claim 5 is injected into cracks that have occurred in at least one structure selected from the group consisting of concrete, asphalt concrete, mortar, wood, and metal, and then the repair area is irradiated with UV light to visualize the repair history.

[0071] A known method can be used for UV irradiation, for example, a method of irradiating a structure with a lamp having a light source in the range of 300 nm to 400 nm. A specific example of the light source is UVGL-58 manufactured by Funakoshi, which is a UV lamp having a wavelength of 365 nm. However, the UV lamp may contain a wavelength other than 365 nm. EXAMPLES

[0072] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0073] (raw materials) Fluorescent radical polymerizable compound Resonac Corporation: Fancryl FA-512MT; dicyclopentenyloxymethacrylate, Shin-Nakamura Chemical Co., Ltd.: NK-Ester A-MO; acryloylmorpholine MIRAMER: M141 Phenoxyethyl Methacrylate, Kyoei Chemical Co., Ltd.: Light Ester 2EG; Diethylene glycol dimethacrylate Kyoei Chemical Co., Ltd.: Light Ester EG; Ethylene glycol dimethacrylate Kyoei Chemical Co., Ltd.: Light Ester 4EG; PEG#200 dimethacrylate

[0074] (Evaluation method) [Casting properties] A 1 mm thick spacer was sandwiched between two glass plates to prevent the resin from leaking from the gaps at the bottom and sides, and the plate was left at room temperature for 24 hours, after which the curable resin composition prepared in the Examples and Comparative Examples described below was poured into the plate from above. After 12 hours at room temperature, the plate was post-cured at 120°C for 2 hours to obtain a cured resin. The tensile strength of the obtained cured resin was measured in accordance with JISK-7161.

[0075] [Visibility of repair history] A concrete cylinder with a diameter of 100 mm and a height of 200 mm was prepared for the crack injection repair test. The cylinder was split vertically and fixed so that the crack width was 0.1 to 0.5 mm, and the sides were sealed with a sealant. A washer was attached to the crack on the upper surface, and the crack injection material prepared in the example was injected into the crack on the lower surface in a 5°C environment using an injector until it spread to the crack on the lower surface. After hardening for more than 2 hours in a 5°C environment, the sealant on the side was peeled off, and 365 nm UV was irradiated to evaluate the visualization state of the repair history based on the presence or absence of fluorescence in the crack repaired part. Those that emitted fluorescence to the extent that the repair status was clearly visible were marked with ◎, those that emitted fluorescence to the extent that the repair status was somewhat visible were marked with ◯, and those that could not confirm fluorescence were marked with ×.

[0076] "Synthesis of fluorescent radical reactive resin" (Synthesis Example 1) A reactor equipped with a stirrer, a reflux condenser, a gas inlet tube and a thermometer was charged with 151 g of bisphenol A type epoxy resin (Mitsui Chemicals Epomic (trademark) R140P, equivalent weight 189), 188 g of 1,6-hexanediol diglycidyl ether (equivalent weight 157), 129 g of trimethylolpropane diallyl ether, 91 g of tetrahydrophthalic anhydride, and 434 g of dicyclopentenyloxyethyl methacrylate, and the temperature was raised to 90 ° C. While maintaining the temperature, 1.0 g of 2,4,6-tris (dimethylaminomethyl) phenol and 0.3 g of methyl hydroquinone were added, and the temperature was raised to 110 ° C. while flowing air, and the reaction was carried out. When the acid value reached 25 mg KOH / g, 120 g of methacrylic acid and 1.0 g of 2,4,6-tris (dimethylaminomethyl) phenol were added, and the temperature was raised to 130 ° C. The reaction was continued while maintaining that temperature, and was terminated when the acid value reached 14 mgKOH / g, yielding a mixture of dicyclopentenyloxyethyl methacrylate, a fluorescent radically polymerizable compound (B1), and a radically reactive resin (A).

[0077] Next, 1.1 g of paraffin wax at 125° F. and three types of fluorescent radical polymerizable compounds, 670 g of phenoxyethyl methacrylate and 167 g of acryloylmorpholine, were added to this radical reactive resin, thereby obtaining a resin component P1 containing 65% by mass of the fluorescent radical polymerizable compound.

[0078] [Table 1]

[0079] (Synthesis Example 2) A reaction apparatus equipped with a stirrer, reflux condenser, gas inlet tube, and thermometer was charged with 226 g of 4-4'-diphenylmethane diisocyanate, 610 g of polypropylene glycol, 320 g of acryloylmorpholine, 576 g of methoxyethyl methacrylate, and 0.3 g of hydroquinone, and the temperature was raised to 60°C while air was being passed through. While maintaining the temperature, 0.02 g of dibutyltin diacrylate was added. The temperature was then raised to 70°C and the reaction was allowed to proceed. As a result of infrared absorption spectrum measurement (IR measurement), the wave number was 2270 cm -1 and wave number 1730cm -1 When no change was observed in the peak ratio, 82 g of 2-hydroxyethyl methacrylate was added, followed by 0.06 g of dibutyltin diacrylate, and the temperature was raised to 75° C. to react. IR measurement showed a wave number of 2270 cm -1 The reaction was terminated when it was confirmed that the peak had disappeared, thereby obtaining a mixture of acryloylmorpholine, which is a fluorescent radical polymerizable compound (B1), methoxyethyl methacrylate, which is a non-fluorescent radical polymerizable compound (B2), and a radical polymerizable resin (A).

[0080] Next, 832 g of dicyclopentenyloxyethyl methacrylate, which is a fluorescent radical polymerizable compound, and 448 g of lauryl methacrylate and 96 g of methyl methacrylate, which are non-fluorescent radical polymerizable compounds, were added to the radical reactive resin, thereby obtaining a resin component P2 containing 36% by mass of the fluorescent radical polymerizable compound.

[0081] (Synthesis Example 3) A reaction apparatus equipped with a stirrer, reflux condenser, gas inlet tube, and thermometer was charged with 226 g of 4-4'-diphenylmethane diisocyanate, 610 g of polypropylene glycol, 320 g of diethylene glycol dimethacrylate, 576 g of methoxyethyl methacrylate, and 0.3 g of hydroquinone, and the temperature was raised to 60°C while air was being passed through. While maintaining the temperature, 0.02 g of dibutyltin diacrylate was added. The temperature was then raised to 70°C and the reaction was allowed to proceed. As a result of infrared absorption spectrum measurement (IR measurement), the wave number was 2270 cm -1 and wave number 1730cm -1 When no change was observed in the peak ratio, 82 g of 2-hydroxyethyl methacrylate was added, followed by 0.06 g of dibutyltin diacrylate, and the temperature was raised to 75° C. to react. IR measurement showed a wave number of 2270 cm -1 The reaction was terminated when it was confirmed that the peak had disappeared, thereby obtaining a mixture of diethylene glycol dimethacrylate, which is a fluorescent radical polymerizable compound (B1), methoxyethyl methacrylate, which is a non-fluorescent radical polymerizable compound (B2), and a radical polymerizable resin (A).

[0082] Next, 832 g of diethylene glycol dimethacrylate, which is a fluorescent radical polymerizable compound, and 448 g of lauryl methacrylate and 96 g of methyl methacrylate, which are non-fluorescent radical polymerizable compounds, were added to this radical reactive resin, thereby obtaining a resin component P3 containing a total of 1152 g of the fluorescent radical polymerizable compound (B1), that is, a total of 36 mass % of the fluorescent radical polymerizable compound.

[0083] (Synthesis Examples 4 to 16) Using the blending amounts of Synthesis Examples 4 to 16 shown in Table 2, resin components P4 to P18 shown in Table 2 were obtained in the same manner as in Synthesis Example 3.

[0084] (Synthesis Example 17) A reaction apparatus equipped with a stirrer, reflux condenser, gas inlet tube, and thermometer was charged with 226 g of 4-4'-diphenylmethane diisocyanate, 610 g of polypropylene glycol, 320 g of diethylene glycol dimethacrylate, 576 g of methoxyethyl methacrylate, and 0.3 g of hydroquinone, and the temperature was raised to 60°C while air was being passed through. While maintaining the temperature, 0.02 g of dibutyltin diacrylate was added. The temperature was then raised to 70°C and the reaction was allowed to proceed. As a result of infrared absorption spectrum measurement (IR measurement), the wave number was 2270 cm -1 and wave number 1730cm -1 When no change was observed in the peak ratio, 82 g of 2-hydroxyethyl methacrylate was added, followed by 0.06 g of dibutyltin diacrylate, and the temperature was raised to 75° C. to react. IR measurement showed a wave number of 2270 cm -1 The reaction was terminated when it was confirmed that the peak had disappeared, thereby obtaining a mixture of diethylene glycol dimethacrylate, which is a fluorescent radical polymerizable compound (B1), methoxyethyl methacrylate, which is a non-fluorescent radical polymerizable compound (B2), and a radical polymerizable resin (A).

[0085] Next, 318 g of diethylene glycol dimethacrylate, which is a fluorescent radical polymerizable compound, and 448 g of lauryl methacrylate, 96 g of methyl methacrylate, and 514 g of dicyclopentenyl methacrylate, which are non-fluorescent radical polymerizable compounds, were added to this radical reactive resin. This resulted in a total of 638 g of diethylene glycol dimethacrylate, which is the fluorescent radical polymerizable compound (B1), that is, a resin component P17 containing 20 mass % of the fluorescent radical polymerizable compound in total.

[0086] (Synthesis Example 18) A reaction apparatus equipped with a stirrer, reflux condenser, gas inlet tube, and thermometer was charged with 226 g of 4-4'-diphenylmethane diisocyanate, 610 g of polypropylene glycol, 319 g of diethylene glycol dimethacrylate, 576 g of methoxyethyl methacrylate, and 0.3 g of hydroquinone, and the temperature was raised to 60°C while air was being passed through. While maintaining the temperature, 0.02 g of dibutyltin diacrylate was added. The temperature was then raised to 70°C and the reaction was allowed to proceed. As a result of infrared absorption spectrum measurement (IR measurement), the wave number was 2270 cm -1 and wave number 1730cm -1 When no change was observed in the peak ratio, 82 g of 2-hydroxyethyl methacrylate was added, followed by 0.06 g of dibutyltin diacrylate, and the temperature was raised to 75° C. to react. IR measurement showed a wave number of 2270 cm -1 The reaction was terminated when it was confirmed that the peak had disappeared, thereby obtaining a mixture of diethylene glycol dimethacrylate, which is a fluorescent radical polymerizable compound (B1), methoxyethyl methacrylate, which is a non-fluorescent radical polymerizable compound (B2), and a radical polymerizable resin (A).

[0087] Next, 448 g of lauryl methacrylate, 96 g of methyl methacrylate, and 833 g of dicyclopentenyl methacrylate, which are non-fluorescent radical polymerizable compounds, were added to this radical reactive resin, thereby obtaining a resin component P18 containing a total of 319 g of diethylene glycol dimethacrylate, which is the fluorescent radical polymerizable compound (B1), that is, a total of 10 mass % of the fluorescent radical polymerizable compound.

[0088] (Comparative Synthesis Examples 1 to 4) Using the blending amounts of Comparative Synthesis Examples 1 to 4 shown in Table 2, resin components cP1 to 4 shown in Table 2 were obtained in the same manner as in Synthesis Example 3.

[0089] [Table 2]

[0090] In Table 2, the meaning of each ingredient is as follows: MDI: 4-4´-diphenylmethane diisocyanate PPG: Polypropylene glycol HQ: Hydroquinone KS-1260: Dibutyltin dilaurate HEMA: 2-hydroxyethyl methacrylate NK-Ester A-MO: Acryloylmorpholine Fancryl FA-512MT: Dicyclopentenyloxyethyl methacrylate Light Ester 2EG: Diethylene glycol dimethacrylate Light Ester EG: Ethylene glycol dimethacrylate Light Ester 4EG: PEG#200 dimethacrylate MIRAMER M141: Phenoxyethyl methacrylate Acrylate MT: Methoxyethyl methacrylate MMA: Methyl methacrylate MIRAMER M123: Lauryl methacrylate Fancryl FA-513M: Dicyclopentenyl methacrylate Light Ester BZ: Benzyl methacrylate Light Ester IB-X: Isobornyl methacrylate SM: styrene monomer Aqualon AR-10: Polyoxyethylene styrenated propenyl phenyl ether sulfate ammonium Hitenol NF-08: Polyoxyethylene styrenated phenyl ether sulfate ammonium ester Hitenol LA-10: Ammonium polyoxyethylene lauryl ether sulfate Hitenol LA-12: Ammonium polyoxyethylene lauryl ether sulfate Hitenol NF-08E: Polyoxyethylene oleyl cetyl ether sulfate ammonium ester Aqualon KH-05: Polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium Aqualon KH-10: Polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium Aqualon KN-10: Polyoxyethylene-1-(allyloxymethyl) alkyl ether Aqualon AN-10: Polyoxyethylene styrenated propenyl phenyl ether

[0091] (Examples 1 to 18, Comparative Examples 1 to 5) "Preparation of fluorescent crack injection material (fluorescent resin composition)" Resin components P1 to P18 and cP1 to cP4 obtained in Synthesis Examples 1 to 18 and Comparative Synthesis Examples 1 to 4 were used to prepare compositions shown in Table 3, and fluorescent resin compositions Q1 to 18 and cQ1 to 5 in Examples 1 to 18 and Comparative Examples 1 to 5 were obtained as crack injection materials. The obtained fluorescent resin compositions Q1 to 18 and cQ1 to 5 were evaluated for visualization of repair history by the above-mentioned evaluation method. The radical reactive resins containing the fluorescent radical polymerizable compounds described in Examples 1 to 18 showed good fluorescence. The results are shown in Table 3.

[0092] [Table 3]

[0093] In Table 3, the meaning of each component is as follows: PT-2HE (N,N-di(β-hydroxyethyl)-p-toluidine) (manufactured by Morin Chemical Industry Co., Ltd.): aromatic tertiary amine Niper NS (dibenzoyl peroxide) (NOF Corporation): organic peroxide Epoxy resin (main component A): Konishi Bond E206W (main component) Epoxy resin (main agent B): Konishi Bond E206W (hardener)

[0094] (Comparative Examples 6 to 7) "Preparation of fluorescent crack injection material (fluorescent resin composition)" The resin component cQ1 obtained in Comparative Synthesis Example 1 was used, and the fluorescent resin compositions cQ6 to 7 of Comparative Examples 6 to 7 were prepared as crack injection materials in the same manner as in Comparative Example 1, except that a fluorescent dye (F) (1 mass% ethanol solution of Rhodamine B manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added in the composition shown in Table 4. The obtained fluorescent resin compositions cQ6 to 7 were evaluated for visualization of repair history and tensile strength by the above-mentioned evaluation method. For tensile strength, the strength ratio was calculated by setting the strength of Comparative Example 1 as 100. The fluorescent resin composition cQ1 obtained in Comparative Example 1 was also evaluated in the same manner. In Comparative Examples 6 and 7, the addition of the fluorescent dye (F) made it possible to visualize the repair history, but the strength was significantly reduced. The results are shown in Table 4.

[0095] [Table 4]

[0096] In Table 4, the meaning of each component is as follows: PT-2HE: Aromatic tertiary amine Niper NS organic peroxide

Claims

1. A fluorescent resin composition comprising a radical-reactive resin (A) and a radical-polymerizable unsaturated monomer (B), wherein the radical-polymerizable unsaturated monomer (B) contains a fluorescent radical-polymerizable compound (B1).

2. 2. The fluorescent resin composition according to claim 1, wherein the fluorescent radical polymerizable compound (B1) is a compound that emits fluorescence when irradiated with light having a wavelength of 365 nm.

3. 3. The fluorescent resin composition according to claim 1, wherein the fluorescent radical polymerizable compound (B1) contained in the radical polymerizable unsaturated monomer (B) is 10 to 95 mass % relative to 100 mass % of the total amount of the radical reactive resin (A) and the radical polymerizable unsaturated monomer (B).

4. The fluorescent resin composition according to claim 1 or 2, wherein the fluorescent radical polymerizable compound (B1) is at least one selected from the group consisting of dicyclopentenyloxy methacrylate, acryloylmorpholine, phenoxyethyl methacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, 2-ethylhexyl methacrylate, and PEG#200 dimethacrylate.

5. The fluorescent resin composition according to claim 1 or 2, further comprising a fluorescent surfactant.

6. A fluorescent crack injection material comprising the fluorescent resin composition according to claim 1 or 2.

7. A crack injection method comprising the steps of injecting the fluorescent crack injection material described in claim 6 into a crack that has occurred in at least one structure selected from the group consisting of concrete, asphalt concrete, mortar, wood, and metal, and then hardening the material.

8. A crack injection repair method, comprising: injecting the fluorescent crack injection material described in claim 6 into a crack that has occurred in at least one structure selected from the group consisting of concrete, asphalt concrete, mortar, wood, and metal; and irradiating the crack with ultraviolet light to visualize the progress of the injection work.

9. A method for managing crack repair, comprising injecting the fluorescent crack injection material described in claim 6 into cracks that have occurred in at least one structure selected from the group consisting of concrete, asphalt concrete, mortar, wood, and metal, allowing it to harden, and then irradiating the repair area with ultraviolet light to visualize the repair history.

Citation Information

Patent Citations

  • Method for identifying repair part, and repair material and method for it

    JP2009235778A

  • Inspection tool and inspection method

    JP2011185629A

  • Method for detecting repaired cracked portion of concrete structure

    JP2013079505A

  • Concrete structure crack survey method and crack survey system

    WO2016006049A1